Monitoring Intensity and Stakeholders’ Orientation: How Does Governance Affect Social and Environmental Disclosure? - Mallin, Chris A. 1957-; Michelon, Giovanna; Raggi, Davide (2013)
The aim of the paper is to investigate the effects of the corporate governance model on social and environmental disclosure (SED). We analyze the disclosures of the 100 U.S. Best Corporate Citizens in the period 2005–2007, and we posit a series of simultaneous relationships between different attributes of the governance system and a multidimensional construct of corporate social performance (CSP). We consider both the extent and the quality of SED, with the purpose of identifying increasing levels of corporate commitment to stakeholders and shedding some light on whether SED is used as a signal or rather as a legitimacy tool. Our empirical evidence shows that the stakeholders’ orientation of corporate governance is positively associated with CSP and SED. On the other hand, we do not find support for the monitoring intensity of corporate governance being negatively associated with social performance. We also find that CSP in the “product” dimension is positively associated with the extent and quality of SED whilst CSP in the “people” dimension is negatively associated with the extent and quality of SED. At a time when shareholders and stakeholders share more common aspects in their relationships with firms, this is a significant area to explore and this research fills an important lacuna in this respect.
Keywords: Structural Equation Modeling; Monitoring; Social and environmental disclosure; Corporate Social Responsibility; Corporate Governance